Pendamping Pelayanan di Mall Pelayanan Publik Dalam Meningkatkan Partisipasi Masyarakat di Kota Sidoarjo - Farsya Salsabila Putri; Achluddin Ibnu Rochim (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
The service assistance carried out at the Sidoarjo Public Service Mall is one of the efforts to increase public participation in Sidoarjo city. With the presence of the August 17, 1945 University student internship program at the Public Service Mall, the community can be assisted by the services provided by various government agencies and use the best facilities and infrastructure in providing services. The service assistance carried out by the Public Service Mall has a positive impact on the community, making it easier to manage services both online and offline. This activity aims to provide an understanding to the community about the services provided by the government. The results of the analysis of internship activities carried out at the Public Service Mall provide understanding and service assistance guarantee top quality and class, as well as providing services by providing easy access for the community. Services provided include various offices, such as the Investment and Integrated One-Stop Service Office, the Population and Civil Registry Office, the Social Service, the Regional Tax Service Agency, and others.